2018
DOI: 10.1186/s41205-018-0033-8
|View full text |Cite
|
Sign up to set email alerts
|

3D printing for congenital heart disease: a single site’s initial three-yearexperience

Abstract: Background3D printing is an ideal manufacturing process for creating patient-matched models (anatomical models) for surgical and interventional planning. Cardiac anatomical models have been described in numerous case studies and journal publications. However, few studies attempt to describe wider impact of the novel planning augmentation tool. The work here presents the evolution of an institution’s first 3 full years of 3D prints following consistent integration of the technology into clinical workflow (2012–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 50 publications
0
45
0
1
Order By: Relevance
“…Studies support the clinical value of 3D-printed models in CHD, specifically with reported usefulness of 3D printing in pre-surgical planning and simulation of complex situations (9,18,(23)(24)(25). Although most of the current literature on 3D printing in CHD is dominated by case reports and case series, emerging evidence based on randomized controlled trials and multicenter studies further confirms its incremental value over traditional visualization tools (26)(27)(28)(29)(30)(31).…”
Section: D-printed Models In Chdmentioning
confidence: 79%
“…Studies support the clinical value of 3D-printed models in CHD, specifically with reported usefulness of 3D printing in pre-surgical planning and simulation of complex situations (9,18,(23)(24)(25). Although most of the current literature on 3D printing in CHD is dominated by case reports and case series, emerging evidence based on randomized controlled trials and multicenter studies further confirms its incremental value over traditional visualization tools (26)(27)(28)(29)(30)(31).…”
Section: D-printed Models In Chdmentioning
confidence: 79%
“…We only used pure white material to simply show the structure of the ventricular septal defect. Studies [22,23] have demonstrated color coding models may result in more intuitive representations. For example, blue and red rendering for veins and arteries, respectively, are often used in clinical medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of 3D printing in interventional Cardiology is expending especially in the field of transcatheter pulmonary valve replacement. Use of 3D technology (including printing) has been shown for describing the vessels anatomy and guiding the surgical approach for intra-cardiac complex anatomy [18,19]. The 3D anatomical models showed a trend for reduced operating room time when compared with similar surgeries.…”
Section: Imaging and Helping Toolsmentioning
confidence: 99%